Implementasi Behavior Dinamis dalam Skenario Adaptif Menggunakan Metode FSM pada Platformer Game - Herdian Rizkiansyah (JURIKOM (Jurnal Riset Komputer), 2018)
In game platforms or commonly categorized into action genre games, the ability to control characters well is needed, such as coordination between eyes, brain and hands needed to complete several stages in the game. On the gaming platform the level of difficulty becomes a thing that is often questioned by the players, such as a low difficulty level will make the player becomes easy to play and the boredom of the game will appear. For that a dynamic behavior will affect the playing experience of the player, not only in the dynamic behavior of some obstacles, the items and the action in the game will not be easy to guess, the dynamic behavior will be shaped into scenarios that have been designed into the game, so players will continue to work by playing and setting strategies to bypass the dynamic behavior. The use of an FSM-based intelligent agent (finite state machine) in this study to develop dynamic behavior as one of the important elements to increase the interest in playing from the player. This study discusses the development of intelligent agents using the Finite State Machine method in shaping dynamic behavior in adaptive scenarios implemented in games with Action Genre - Game Platform.